FERMENTASI Aspergilus sp UNTUK PENINGKATAN RENDEMEN DAN MUTU MINYAK ATSIRI LIMBAH INDUSTRI SIRUP KALAMANSI - Tuti Tutuarima; Dewi Handayani; Budiyanto Budiyanto; Ade Tri Hartawi (Universitas Andalas, 2022)
Orange peel is one of byproduct from the kalamansi syrup industry. Orange peel oil is stored in the oil gland of the skin (flavedo). Orange peel contains cellulose, hemicellulose, pectin and other components. Degradation carried out by biological agents such as bacteria and fungi can increase oil yield. This study aimed to determine the effect of fermentation time and the amount of inoculum on the yield of orange oil. This study consisted of two factors, namely the length of fermentation (2 days, 4 days, 6 days) and the number of inoculums (2.5%, 5%, 7.5%). The data obtained were analyzed using ANOVA and DMRT methods. The results showed that the length of fermentation time and the number of inoculums had a significant effect on the increase in yield and had no significant effect on the quality characteristics of the essential oil of kalamansi orange peel. The highest yield was obtained at 4 days fermentation with an inoculum of 7.5%.